Vibration properties of wood - Rani, Anak Kaba (Universiti Malaysia Sarawak, UNIMAS, 2006)
The potential of local wood such as Alan Bunga, Selangan Batu, Belian, Damar Minyak and White Meranti for musical instruments were investigated. Their physical and mechanical properties were determined in order to obtain their characteristics.